EFFECTIVENESS OF THE AQUATIC PLANT Azolla microphylla FOR REDUCING CONTAMINANTS IN TOFU LIQUID WASTE - Fahriansyah, Rifan; Hasan, Zahidah; Rochima, Emma; Arief, Mochamad Candra W. (Jurusan Perikanan dan Kelautan, 2025)
One of the industrial activities that produces a lot of liquid waste is the tofu industry. Most of the liquid waste from industry flows directly into the sewer without prior treatment. This research aimed to determine the best plant biomass for reducing contaminants in tofu liquid waste. This research used an experimental method with a completely randomized design with 4 treatments and 3 replications, namely A (without addition of Azolla), B (addition of Azolla 250 grams), C (addition of Azolla 3000 grams), and D (addition of Azolla 350 grams). Tofu waste samples were obtained from the Cheese Tofu Factory located in the Cibuntu Tofu Industrial Center, Bandung City. The results of research for 15 days showed that the addition of Azolla microphylla could reduce the levels of contaminants in tofu liquid waste. The addition of 300 grams of Azolla microphylla plants to the phytoremediation process provided the best reduction in contaminants in tofu liquid waste by reducing BOD concentrations by 61%, nitrate by 77.49%, and phosphate by 68.44%.Keywords: Azolla microphylla, phytoremediation, tofu industry.